2013
DOI: 10.1159/000347219
|View full text |Cite
|
Sign up to set email alerts
|

When Size Matters: Diagnostic Value of Kidney Biopsy according to the Gauge of the Biopsy Needle

Abstract: Background: Kidney biopsy is a vital tool in the diagnosis of kidney disease. Although it has become a routine procedure, it is not complication-free. Some serious complications of percutaneous kidney biopsy include retroperitoneal hemorrhage and death. There is an increased belief that smaller biopsy needle size results in a lower complication rate. As renal pathologists, we witness an increased number of kidney biopsies performed with a small needle size (as low as gauge 22), which results in inadequate tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 32 publications
(25 reference statements)
3
44
0
2
Order By: Relevance
“…The reason for the higher major complication and transfusion rates in our study compared to others may have to do with many factors, including the prospective nature of our study, the patient mix and the fact that as an academic institution the majority of biopsies are performed by supervised fellows in training. It is therefore of interest that our transfusion rate of 5.3% is similar to rates (5.4-8%) recently reported in a number of biopsy studies from other major academic institutions that used smaller-gauged needles [22,45,46]. Roth et al [45] evaluated 149 native PRBs performed over a 1-year period using 16- and 18-gauge automated needles and found the post-PRB transfusion rate to be 5.4% overall and not different between the needles (4.9 and 6.0%, respectively).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The reason for the higher major complication and transfusion rates in our study compared to others may have to do with many factors, including the prospective nature of our study, the patient mix and the fact that as an academic institution the majority of biopsies are performed by supervised fellows in training. It is therefore of interest that our transfusion rate of 5.3% is similar to rates (5.4-8%) recently reported in a number of biopsy studies from other major academic institutions that used smaller-gauged needles [22,45,46]. Roth et al [45] evaluated 149 native PRBs performed over a 1-year period using 16- and 18-gauge automated needles and found the post-PRB transfusion rate to be 5.4% overall and not different between the needles (4.9 and 6.0%, respectively).…”
Section: Discussionsupporting
confidence: 85%
“…However, in the prospective trial by Nicholson et al [37], no differences in complication rates were found for biopsies performed with 14-, 16- or 18-gauge automated needles. Similarly, a number of other studies have found no differences in complication rates or transfusion requirements based on needle size [4,8,11,21,32,44,45], including the 2013 report of the Norwegian Kidney Biopsy Registry [21] of 9,288 PRBs. However, in a recent meta-analysis by Corapi et al [12], the rate of transfusion was greater in patients biopsied with a 14-gauge automated needle compared to 16- and 18-gauge needles (2.1 vs. 0.5%, p = 0.009), and this led to the recommendation that the use of 14-gauge needles be discouraged.…”
Section: Discussionmentioning
confidence: 88%
“…Although the overall incidence of requiring a blood transfusion in this meta-analysis was 0.9% (95% confidence interval, 0.4% to 1.5%), transfusion rates as high as 5%-9% have been described in large single-center case series from major academic centers (7,12,(35)(36)(37). This may be because of some PRBs being performed by nephrology trainees and more high-risk patients undergoing PRBs at large academic centers.…”
Section: Bleedingmentioning
confidence: 82%
“…The diagnostic yield does not seem to differ significantly when comparing 14-and 16-gauge needles, but some (although not all) studies indicate lower yield with smaller (18-gauge) needles (6)(7)(8)(9)(10)(11)(12). Other factors, such as patient characteristics (e.g., kidney size) and operator experience, may also affect diagnostic yield.…”
Section: Biopsy Technique and Operator The Percutaneous Renal Biopsymentioning
confidence: 99%
“…Overall, 14-gauge needles did not improve histological assessment, yet tended to create more complications. Smaller sized needles (16-18 gauge) are sufficient with lower complication rates, while further size reduction compromises histological assessment [29][30][31][32].…”
Section: Issues Related To Histological Workupmentioning
confidence: 99%